Small And Medium Enterprises (SMES) Performance In Aceh Jaya, Indonesia - Oriza, Rahmat (2018)
SMEs in Aceh Jaya plays prominent role in the development of local economy with regard to income generation, poverty eradication, and employment opportunities. But at present, SMEs are facing vast competition within the local markets and unfavorable government policy towards SMEs growth. As such SMEs performance are essential to determine the livelihood of SMEs. Hence, this study aims to measure the performance of SMEs in Aceh Jaya, assess owners and business characteristics in influencing SMEs performance and measure structural relationship of variables on SMEs performance. 260 SMEs owners were involved in the study survey. Survival Index Value (SIV) prescribed by Abouzeedan and Busler (2004) was the main measurement of SMEs in Aceh Jaya.